Enhancing Vanilla Planifolia Generative Phase via IoT-Based Microclimate Control - Galushasti, Andarula; Wardana, Rudi; Wardati, Irma; Hidayat, Taufik; Malika, Uyun Erma; Rizaldi, Taufiq (Universitas Panji Sakti, 2025)
Vanilla (Vanilla planifolia) is one of the agricultural commodities with high economic value, but its cultivation faces various challenges, including climate change and suboptimal environmental management. Conventional microclimate control methods are primarily manual and reactive, often failing to maintain stable conditions during the critical phase of generation. Technological innovations, especially IoT-based microclimate controllers, enable real-time monitoring and automated regulation of temperature, humidity, and light, thereby reducing environmental fluctuations that negatively affect flowering and yield. This research aims to develop and apply an IoT-based microclimate controller that optimizes growth conditions during the generative phase of vanilla, and to evaluate its impact on growth and crop yields. The study was conducted over a 3-month generative period, using 30 vanilla plants per group (n = 60 in total), with three replications. Data were collected weekly and analyzed using descriptive statistics and t-tests to compare growth and yield performance. The results show that IoT-based microclimate controllers significantly improved optimal temperature and humidity stability, increasing plant growth and crop yields. The average stem length and number of flowers per plant increased by 30% and 25%, respectively, compared to the control group, while vanillin content rose from 1.8% to 2.5%. These findings offer new insights into sustainable vanilla cultivation management, which can be adopted by farmers to enhance productivity and quality. Recommendations for further research include developing more advanced systems, conducting cost-benefit analyses, and applying these technologies in different climatic conditions.